2021
DOI: 10.1007/s12640-021-00329-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of 4-CMC and 4-MeO-PVP in DBA/2J Mice After Acute and Intermittent Administration and Following Withdrawal from Intermittent 14-Day Treatment

Abstract: Synthetic cathinones appeared on the market in the 2000s as new psychoactive substances and gained significant prevalence among drug abusers. Cathinones produce psychostimulant and empathogenic effects by enhancing dopaminergic, noradrenergic, and serotoninergic neurotransmission in the brain, and those which potently and selectively enhance dopaminergic transmission are considered to have higher abuse potential. The present study examines the behavioral effects related to psychostimulant properties, abuse pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In conclusion, it was confirmed that the effect on locomotory activity is common across different types of synthetic cathinones [ 23 , 30 , 33 , 36 , 41 , 42 , 57 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 63%
“…In conclusion, it was confirmed that the effect on locomotory activity is common across different types of synthetic cathinones [ 23 , 30 , 33 , 36 , 41 , 42 , 57 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 63%
“…In understanding the neurobiology of addiction and neuropharmacological action of psychoactive plants, CPP model is established to evaluate the reinforcing abilities of a psychoactive substance-paired paradigm against a psychoactive substance-free paradigm (Möller et al, 2018;Wojcieszak et al, 2021). The CCP paradigm is principled on the theory that a textual stimulus can attain secondary appetitive ability when paired with a primary reinforcer, thus indicating abuse liability (Aguilar et al, 2009;Strekalova, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…4-CMC also affects intracranial selfstimulation (ICSS) in rats (Bonano et al, 2015) in a manner that suggests potential for abuse. Wojcieszak et al (2020Wojcieszak et al ( , 2021 reported that 4-CMC increases locomotor activity in mice, but does not engender conditioned place preference (CPP), a measure of potential rewarding effects. 4-CMC is reported to have toxic effects (Luethi et al, 2019;Zhou et al 2020) and has been detected in samples taken from human drugged driving cases and overdose autopsies (Tomczak et al 2018).…”
Section: Introductionmentioning
confidence: 99%